MENTAL HEALTH IMPACT OF PANDEMIC COVID-19 AMONG HEALTH CARE WORKERS: A SYSTEMATIC REVIEW - David R. I. Hutajulu; Ede S. Darmawan (Journals of Ners Community, 2022)
Basically, this study want to know what is the impact of COVID-19 among Health Care Workers (HCWs), including effect (stress, burnout, and anxiety). This systematic review was performed according to the Preferred Reporting Items for Systematic review. We conducted a systematic review by searching the following databases Proquest, Science Direct, Scopus, Sage, and MDPI from January 2020 to December 2020. The search was limited to the studies that reported mental health impact of COVID-19 in healthcare workers, such as psychological (emotional) trauma, acute stress disorder (ASD) and post-traumatic stress disorder (PTSD), mass traumatic event, secondary traumatic stress (STS), moral injury, sleep disorder. Case reports, duplicate publications, journal reviews, were excluded. The methodological quality of studies was assessed by the Appraisal tools From JBI tools. The initial search returned 34 articles. twelve studies were included in final analysis, with total of 14.205 subjects. Healthcare worker directly giving healthcare to suspected or confirmed COVID-19 patients may develop various mental issues such as anxiety, poor sleep quality, insomnia, parasomnia, changing personal life and enhanced negative effect. Physician and Nurse are healthcare workers professions most at risk of infection of COVID-19. Healthcare Workers have significant mental pressure during the COVID-19 pandemic. The different healthcare workers professions and gender have different levels of risk of mental disorders during COVID-19 pandemic.